Organ-specific proteome analysis for identification of abiotic stress response mechanism in crop - Komatsu, Setsuko; Hossain, Zahed (Frontiers in Plant Science, 2013)
Abiotic stresses, such as flooding, drought, salinity, and high/low temperatures, are the major constraints that global crop production faces at present. Plants respond to a stress by modulating abundance of candidate proteins, either by up-regulating expression or by the synthesizing novel proteins primarily associated with plant defense system. The cellular mechanisms of stress sensing and signal transduction into cellular organelles have been reported. Nevertheless, the responses of plant cells to abiotic stresses differ in each organ. As the correlation between the expression of mRNAs and the abundance of their corresponding proteins is difficult to assess in specific organs, proteomics techniques provide one of the best options for the functional analysis of translated regions of the genome. The present review summarizes the organ-specific proteome analyses for better understanding of the response mechanisms of crops to abiotic stresses, including flooding, drought and salinity. The differential organ specific responses against each of these stresses are discussed in detail to provide new insights into plant stress response mechanisms at protein level.